Kritik Sosial dalam Cerpen Manuel Karya Seno Gumira Ajidarma Tinjauan Sosiologi Sastra - Perdana, Adhi Dian; Alfiana, Nila; Ramadhani, Nur Fadhilah Rizqi; Yuliani, Nur Indah; Putri, Widya Ryolita (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
Orde Baru was the reign of President Soeharto which brought about a change in order over people's lives. In the 16th century East Timor was colonized by the Portuguese, then in 1975, East Timor proclaimed its independence and Indonesia made this territory of East Timor as the 27th province. Over time, conflicts arose between the Indonesian government and the people of East Timor who wanted independence. In the conflict, Indonesia became the object of conflict while the people of East Timor were made the subject of conflict. The conflict made the writer Seno Gumira Ajidarma moved to write works that represented the social life of his people. The work raised several issues of the Orde Baru government was the anthology book Saksi Mata which contained 13 short stories. In the anthology, there is a short story